(untitled) (Bangladesh Journal of Agriculture, 2024)
Water melon is popular summer fruits and gummy stem blight (GSB) disease caused by fungal pathogen Didymella bryoniae is one the major problem for water melon production in Bangladesh. With the increase of watermelon cultivation in the country, gummy stem blight disease is increasing drastically which discouraged farmers watermelon production. Using resistant source is most effective disease management strategy compared to other disease management methods. The seed health test revealed the presence of D. bryoniae and F. oxysporum f.sp. niveum fungi associated with water melon seeds imported from different counties. BARI line 03-144x21 and BARI line 02-07x08 showed the lowest lesion symptom by 25.67 x 25.17mm and 24.17 x 23.67mm in laboratory detached leaves test in the artificially inoculated with D. bryoniae isolates S002 and S005, respectively. In pot evaluation test, all BARI lines showed lower gummy stem blight disease incidence and severity which indicated the moderately resistant (MR) against the disease and all the imported hybrid varieties showed moderately susceptible to susceptile against the disease. In the field experiments, four BARI inbreed lines and two commercial varieties (Black Diamond (Metal Seed) and Black Diamond (Alamgir Seed) showed moderately resistant (MR) against the disease. From these studies, it can be concluded that BARI inbred lines viz. BARI line 01-08X07, BARI line 02-07X08, BARI line 03-144X21BARI line 04-21X144, showed moderately resistant against stem blight disease of water melon and all the commercial varieties and advance line showed susceptible of stem blight disease of water melon. Bangladesh J. Agri. 2024, 49(1): 68-85